2013
DOI: 10.5812/jjm.5043
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of AmpC and SHV β-Lactamases in Clinical Isolates of Escherichia coli From Tehran Hospitals

Abstract: Background: Beta-lactam resistance in Gram-negative bacteria, especially Escherichia coli, is a main clinical problem. It is often caused by the coproduction of β-lactamases, particularly extended-spectrum β-lactamases (ESBLs) and AmpC enzymes. It may lead to a problem for diagnosis via recommended phenotypic tests by the Clinical and Laboratory Standards Institute (CLSI). Conversely, β-lactamase genes have several subfamilies; therefore, using designed primers with high ability could be valuable to detect all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
1
9
2
Order By: Relevance
“…A study conducted in northern Iran reported a rate of 7.7% based on phenotypic methods (16). In another study in Tehran, 10.2% of E. coli isolates were AmpC-positive according to the PCR method (17). The lower prevalence compared to our results could be due to differences in PCR assay design, as the abovementioned studies did not apply primers for detecting DHA and MOX genes in the assay protocol (17).…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…A study conducted in northern Iran reported a rate of 7.7% based on phenotypic methods (16). In another study in Tehran, 10.2% of E. coli isolates were AmpC-positive according to the PCR method (17). The lower prevalence compared to our results could be due to differences in PCR assay design, as the abovementioned studies did not apply primers for detecting DHA and MOX genes in the assay protocol (17).…”
Section: Discussioncontrasting
confidence: 76%
“…This needs special attention because it may indicate the spread of PMABL-producing strains in the community, as some other studies have suggested (2,8). The prevalence of ESBLproducing isolates was 49% in our study, which is a little lower than the rates of 57% and 52% previously reported in Iran (16,17).…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…The rate of resistance to imipenem was very low; this is similar to the results of others studies conducted in Iran and worldwide. Thus, imipenem is still the most active agent against ESBL and AmpC-β-lactamase-producing E. coli isolates (2,(26)(27)(28). However, in the present study, two isolates were found to be resistant to imipenem; thus, resistance to this antibiotic may increase in the future (2,29).…”
Section: Discussionmentioning
confidence: 52%